Effects of a comprehensive nursing intervention based on ERAS principles on postoperative outcomes in patients undergoing laparoscopic cholecystectomy: a randomized controlled trial - Zhang, Dingfeng; Zhang, Ting (Frontiers in Surgery, 2025)
ObjectiveTo assess the impacts of comprehensive nursing on pain score, negative mood along with quality of life in patients undergoing laparoscopic cholecystectomy (LC).MethodsEighty-four patients (aged 40–65 years) who underwent LC in our hospital from March 2023 to March 2024 were chosen to be the study objects and were randomly separated into control group and study group. The control group accepted routine nursing. The study group accepted comprehensive nursing. The perioperative indicators, degree of pain, inflammatory response, anxiety and depression, sleep quality, incidence of postoperative complications, quality of life, as well as nursing satisfaction were compared in both groups.ResultsThe perioperative indicators of the study group were significantly better than those of the control group (P < 0.01), and the improvements in postoperative pain, inflammatory response, sleep quality, psychological state, and quality of life were more pronounced (all P < 0.05), with a lower incidence of complications (7.14% vs. 26.18%) and higher nursing satisfaction (95.24% vs. 76.19%).ConclusionComprehensive nursing can accelerate postoperative recovery, reduce the degree of pain, reduce inflammatory response, improve negative mood and sleep quality, decrease the incidence of postoperative complications along with promote the quality of life in patients undergoing LC. These findings suggest that comprehensive nursing should be considered as a standard care approach to optimize recovery for patients undergoing laparoscopic cholecystectomy.